2016
DOI: 10.1111/mmi.13329
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell characterization of metabolic switching in the sugar phosphotransferase system ofEscherichia coli

Abstract: The utilization of several sugars in Escherichia coli is regulated by the Phosphotransferase System (PTS), in which diverse sugar utilization modules compete for phosphoryl flux from the general PTS proteins. Existing theoretical work predicts a winner-take-all outcome when this flux limits carbon uptake. To date, no experimental work has interrogated competing PTS uptake modules with single-cell resolution. Using time-lapse microscopy in perfused microchannels, we analyzed the competition between N-acetyl-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…For this purpose, we constructed a strain that contains an EI-mCherry fusion, expressed from the native chromosomal locus, as well as mCerulean gene under the regulation of N-acetyl glucosamine (NAG) promoter ( Pnag ). To induce expression from Pnag promoter, phosphorylated NAG needs to be present inside the cell (Yamada and Saier, 1988 ; Westermayer et al, 2016 ). Since EI is the first protein in the phosphorylation cascade that enables uptake and phosphorylation of PTS sugars, including NAG (Yamada and Saier, 1988 ), expression of mCerulean implies that EI is active.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we constructed a strain that contains an EI-mCherry fusion, expressed from the native chromosomal locus, as well as mCerulean gene under the regulation of N-acetyl glucosamine (NAG) promoter ( Pnag ). To induce expression from Pnag promoter, phosphorylated NAG needs to be present inside the cell (Yamada and Saier, 1988 ; Westermayer et al, 2016 ). Since EI is the first protein in the phosphorylation cascade that enables uptake and phosphorylation of PTS sugars, including NAG (Yamada and Saier, 1988 ), expression of mCerulean implies that EI is active.…”
Section: Resultsmentioning
confidence: 99%
“…SUT201, which expresses EI-mCherry and ZapA-GFP from the chromosome, was constructed by P1 transduction of zapA-gfp(::cat) from HC261 (Peters et al, 2011 ) to MG1655Φ( ptsI -mCherry). NTS102, which expresses EI-mCherry, Psrl -mVenus and Pnag -mCerulean from the chromosome, was constructed by P1 transduction of MG1655Φ( ptsI -mCherry), linked to KanR, to T1683 (Westermayer et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gene ASU28_RS14105 was down-regulated and ASU28_RS08220 did not expressed in luxS -pMG76e-L-ZS9. PTS is a sugar-phosphorylating system and a complex protein kinase system that regulates a wide variety of metabolic processes and controls the expression of numerous genes (Khajanchi et al, 2015 ; Somavanshi et al, 2016 ; Westermayer et al, 2016 ). It has been reported that AI-2 could be imported through the PTS (Quan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…An additional assay that we used to compare the effect of TmaR subcellular level on PTS sugars uptake relied on the use of a strain expressing mCerulean, a cyan fluorescent protein (CFP), from the N-acetyl glucosamine (NAG) promoter (P NAG ) and EI-mCherry (31). NAG has been used in the past as a representative of PTS sugars, whose utilization is positively regulated by EI, since induction of P NAG by NAG is consistent with the positive feedback mechanism suggested for promoters of PTS sugar utilization genes (31) (15). Hence, production of mCerulean from P NAG implies that EI is active and enables estimation of EI activity by fluorescence microscopy.…”
Section: Tmar-mediated Ei Localization Affects Sugar Uptake By the Ptmentioning
confidence: 99%